Analysis of Human in Works of Moniro Ravanipor - Dorsani, Mojdeh; Amirahmadi, Aboalghasem; Sardehi, Ali Eshghi (Journal of History Culture and Art Research, 2017)
Abstract The novel and fiction belong to a field of literary creation, which is neither involved in reasoning like social and philosophical sciences, nor is independent from practical and routine life of people like poetry and legend. Accordingly, the novel has the highest capability to represent the life of contemporary man. Moniro Ravanipor is one of the contemporary writers in the field of novel and story who has created various works in field of patriarchal society and women’s rights protection and paying attention to human pains at the society and other different aspects of human life. In this study, novels and collection of stories of Moniro Ravanipor are analyzed with an emphasis on description of human patterns, humanistic manifestations, and human reflections on her works.